Medie imprese italiane: un’indagine sui valori d’impresa - Ciambotti, Massimo; Palazzi, Federica (Piccola Impresa / Small Business, 2015)
The aim of this research work is to investigate the personal values of entrepreneur, as well as the deriving family and entrepreneurial values, which have oriented and guided the action of entrepreneur who has chosen to drive the firm in the medium size, through a qualitative and quantitative development project. The knowledge of these values, which qualify the corporate culture, is useful to fully understand the entrepreneur’s choice of leaving the small size to transit in the medium size. The employed research method is the multiple-case studies. We have deeply examined four Italian medium-sized enterprises, belonging to the leather goods sector. The analyzed firms are independent companies, which have undertaken a gradual, harmonious and systemic development process, without too big dimensional jumps, without organizational upsetting, employing internal financial resources produced by operations management. The development is coherent with the entrepreneur’s values and objectives, who desires to maintain the independence by external controls, to guarantee the long-term continuity of the firm and finally to satisfy the stakeholders’ needs, from clients to co-workers, included the collectivity that lives the territory in which the firm operates. Consistently with the holistic development model of Coda (2010), the social dimension of success is pursued in parallel to the more traditional competitive dimension, linking in the economic-income dimension.